Combination of ataxia telangiectasia and Rad3-related inhibition with ablative radiotherapy remodels the tumor microenvironment and enhances immunotherapy response in lung cancer - Jenny Ling-Yu Chen; Chun-Kai Pan; Li-Cheng Lin; Yu-Sen Huang; Tsung-Hsuan Huang; Shu-Jyuan Yang; Sung-Hsin Kuo; Yu-Li Lin (Cancer Immunology, Immunotherapy)
Abstract We investigated the combined effects of ataxia telangiectasia and Rad3-related (ATR) inhibition, ablative radiotherapy, and immune checkpoint inhibitor (ICI) therapy against lung cancer. ATR inhibitor was administered combined with ablative radiotherapy to assess its radiosensitizing effect on lung cancer cells. Treatment response and survival were evaluated in vivo using A549 xenograft flank tumor and synchronous LLC lung and flank tumor mouse models. Mice received ablative radiotherapy (12 Gy/d for 2 d), ATR inhibitor, and ICI. The tumor microenvironment was assessed in irradiated flank and non-irradiated lung tumors. Programmed death-ligand 1 expression was upregulated after irradiation. ATR inhibition attenuated this upregulation. ATR inhibitor pretreatment decreased cell survival after irradiation by inhibiting DNA double-strand break repair, inducing mitotic cell death, and altering cell cycle progression. ATR inhibition enhanced radiation-induced damage-associated molecular patterns determined by high mobility group box 1 quantification and activated the cyclic GMP-AMP synthase-stimulator of interferon genes pathway. Combined ATR inhibition and ablative radiotherapy inhibited tumor growth and improved survival in mice. Adding ICI therapy further enhanced local antitumor effects, reducing the metastatic lung tumor burden and remodeling the tumor microenvironment through immunogenic cell death induction and enhanced immune cell infiltration. Triple therapy increased immune cell infiltration in distant non-irradiated lung tumors and stimulated the generation of protective T-cell immunity in splenocytes. Safety analysis showed minimal toxicity. ATR inhibition enhanced the efficacy of ablative radiotherapy and immunotherapy in lung cancer. These findings underscore the importance of combination therapies for enhancing systemic antitumor immune responses and outcomes.